Eastern Pigmy Blue, Brephidium isophthalma pseudofoea (Morrison) (Insecta: Lepidoptera: Lycaenidae) - Donald W. Hall; Jerry F. Butler (EDIS)
The eastern pigmy blue is our smallest eastern butterfly. It is found near saltwater—particularly in salt marshes where its host plants occur.  This document is EENY-107, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1999. Reviewed May 2003.